Article Commentary: Secondhand Smoking in Jordan: Clearing the Air for One of the Highest Tobacco Prevalence Countries in the Middle East - Linda G. Haddad; Sukaina Al-Zyoud; Nesrin Abu Baker; Huda Gharaibeh; Omar El Shahawy; Raed Alramadhani (SAGE Publishing, 2011)
As the rate of tobacco consumption in Jordan increases, Jordanian policy makers are urged to develop guidelines on smoking exposures. This paper is concerned with the magnitude of exposure and harm caused by secondhand smoke (SHS) on childbearing women and young children. Despite a strict policy that limits tobacco advertising and efforts by the Ministry of Health, which include cessation programs and education on the adverse effect of smoking, the country sustains its high smoking rate, especially among men. According to the data gathered in this paper, special concern should be directed toward children's SHS exposure. Only four recent studies on SHS exposure among Jordanian women and children were encountered. Moreover, Jordan has legislation that bans smoking in public institutions; however, the enforcement of the law is extremely poor in most locations. Recommendations are presented to aid policy makers and law enforcement agencies in addressing this issue.